2018
DOI: 10.1002/cptc.201800082
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Study of Irradiation Requirements Towards an Efficient Photochemical Wohl‐Ziegler Procedure in Flow

Abstract: A platform has been developed to enable standardization of light sources, allowing consistent scale‐up from high‐throughput screening in batch to flow, using the same pseudo‐monochromatic light source. The impact of wavelength and light intensity on a photochemical reaction was evaluated within this platform using the Wohl‐Ziegler benzylic bromination of 4‐methyl‐3‐(trifluoromethyl)benzonitrile with N‐bromosuccinimide as a model system. It was found that only 40 % of the maximum light intensity was required wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 60 publications
1
38
1
Order By: Relevance
“…CN-OA-m was reused three times after drying at room temperature ( Figure S49-S51). Transferring the photochemo-enzymatic hydroxylation from a total volume of 1 mL in 1.5 mL glass vials successfully to a larger scale (7 mL volume, 10 mL tubes) in another photoreactor (provided by GlaxoSmithKline, S5), [16] showed the robustness and reproducibility of the approach. The hydroxylation of 1 a worked equally well giving up to 7.5 mM of (R)-2 a.…”
mentioning
confidence: 97%
“…CN-OA-m was reused three times after drying at room temperature ( Figure S49-S51). Transferring the photochemo-enzymatic hydroxylation from a total volume of 1 mL in 1.5 mL glass vials successfully to a larger scale (7 mL volume, 10 mL tubes) in another photoreactor (provided by GlaxoSmithKline, S5), [16] showed the robustness and reproducibility of the approach. The hydroxylation of 1 a worked equally well giving up to 7.5 mM of (R)-2 a.…”
mentioning
confidence: 97%
“…A photoreactor meeting these criteria will enable optimization of the light to the chemistry as opposed to optimizing the chemistry to several different light sources, as the process transfers through various stages of development, ensuring consistent results regardless of reaction scale . Herein, we introduce a standardized photochemical platform that has been deployed across GSK, which enables results to be reliably reproduced.…”
Section: Figurementioning
confidence: 99%
“…The Photochemistry LED Illuminator (PHIL, see the Supporting Information for full characterization) is a photoreactor with the capability to screen reactions (up to 48 HPLC vials) and scale‐up in batch (3 x 1–30 mL vials) or flow (4.09 mL reactor volume) all with the same light source (Figure ). Initial validation of this system demonstrated that by utilizing this technology, a more efficient route to scale‐up is achieved as optimization only needs to be performed once . Efficient wavelength optimization is achieved by utilizing a 24‐well screening plate, containing a range of pseudo‐monochromatic wavelengths (365, 385, 405, 420, 450 and 525 nm).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[8] A recent paper by Cantillo et al investigated this reaction using a compact fluorescent lamp (CFL) as the light source. [6] However, improvements on efficiencies can be made, as a paper from Bonfield et al notes that the maximum absorption of NBS is 400 nm, [9] which should allow the use of a lower-energy LED (light-emitting diode) light with a more selective wavelength. Also, the paper notes that only 40 % maximum LED light intensity was required for optimal results.…”
Section: Introductionmentioning
confidence: 99%